2019
DOI: 10.1021/acsami.9b14679
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Si-Promoted Osteogenic Differentiation of BMSCs through Light Illumination

Abstract: Graphene (Gr) presents promising applications in regulating the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Light illumination is regarded as a spatiotemporally controllable, easily applicable, and noninvasive mean to modulate material responses. Herein, Gr-transferred silicon (Gr/Si) with a Schottky junction is utilized to evaluate the visible-light-promoted osteogenic differentiation of BMSCs. Under light illumination, light-induced charges, owing to the formation of the Schott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
(65 reference statements)
1
17
0
Order By: Relevance
“…It is reported that calcineurin/NFAT signaling is a vital regulator of angiogenesis, immune development and function, and osteogenic differentiation. , Recent studies have shown that the genes of the calcineurin/NFAT signaling pathway, such as CaM, CaN, and NFAT, are widely expressed in multiple cell lines (including MC3T3-E1 cells) . Calmodulin (CaM), as a ubiquitous Ca 2+ -binding protein, participates in the regulation of Ca 2+ -sensitive biological events including Ca 2+ transport, transcriptional regulation, and long-term intracellular signaling .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that calcineurin/NFAT signaling is a vital regulator of angiogenesis, immune development and function, and osteogenic differentiation. , Recent studies have shown that the genes of the calcineurin/NFAT signaling pathway, such as CaM, CaN, and NFAT, are widely expressed in multiple cell lines (including MC3T3-E1 cells) . Calmodulin (CaM), as a ubiquitous Ca 2+ -binding protein, participates in the regulation of Ca 2+ -sensitive biological events including Ca 2+ transport, transcriptional regulation, and long-term intracellular signaling .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, a similar result has been reported that when negative potential generated by the poled membrane impacted the osteoblasts, an electric field is induced between the nucleus and the cytoplasm, stimulating the increase of intracellular Ca 2+ ions through cell-membrane VGCCs. 48 The change of intracellular Ca 2+ concentration in MC3T3-E1 cells would act as a second messenger to further activate the downstream calcineurin/ NFAT signaling pathway, which would promote osteogenic differentiation.…”
Section: Tracing Properties By Existing Medical Imagingmentioning
confidence: 99%
“…Then, as-grown monolayer chemical vapor deposition copper matrix Gr (Nanjing Xianfeng Nanometer Material Technology Co., Ltd.) was transferred to the surface of the TN with the assistance of polylactic acid (Changchun Sino-Biomaterials Co., Ltd., crystallized poly(L-lactic acid) (PLA), 20 mg/mL dissolved in methylene dichloride). 22 Briefly, PLA solution was spin-coated on the surface of Gr, and the copper was etched away by ammonium persulfate aqueous solution (Aladdin Chemical Reagent, 0.1 M). The obtained PLA/Gr films were rinsed with deionized water and transferred to the surface of TN/SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Also, under the illumination of visible light, the single layer of graphene can be transferred to the silicon surface, where the Schottky junction was formed. Long et al confirmed that the unique structure at the interface of graphene and Si could change the surface potential of the composites, activate the Ca 2+ signaling pathway, and eventually promote the osteogenic differentiation of BMSCs . Besides, it is observed that graphene itself has a strong adsorption ability, which can be used to deliver osteogenic biomolecules …”
Section: Carbon-based Nanomaterials For Bone and Cartilage Regenerationmentioning
confidence: 99%